Blissful bites : vegan meals that nourish mind, body, and planet - Morgan, Christy (Dallas : BenBella Books, 2011)
"Cooking in a way that's good for you and for the environment-not to mention delicious-doesn't have to be a pain; in fact, it can be sheer bliss. In Blissful Bites: Vegan Meals That Nourish Mind, Body, and Planet, Christy Morgan shows readers how to make healthy, delicious, animal-product free meals without a lot of effort. It's been long-accepted that giving up animal products also means giving up easy and enjoyable cooking, but that's just not true. Blissful Bites is a refreshing introduction to the idea that switching to a plant-based diet that uses locally grown and organic products can be easy and rewarding-for both body and mind. Blissful Bites includes more than 150 recipes that make eating every meal healthier and exciting. Morgan, known to her online audience as The Blissful Chef," also delivers recipes that are easy for the typical home cook to follow, making a plant-based diet seem simpler and more delicious to implement than ever before. Blissful Bites is filled with unique recipes and plenty of tips on how to live a healthier, more environmentally friendly life, without sacrificing an ounce of taste. "--
First things first. Finding your bliss ; How to read this cookbook ; The icons ; Creating the ideal kitchen space and pantry ; Pantry basics ; The tools ; Tips for getting started ; Basic cooking and cutting techniques -- Prepping station -- The recipes. Breakfast and brunch of champions ; Appetizers and soups for every occasion ; Not-your- average fresh salads and dressings ; Delectable vegetable sides ; Whole grains and carbs do a body good ; Sea vegetables, huh? ; Compassionate proteins ; Healthier desserts you crave.
Includes bibliographical references (p. 244-247) and index.
Keywords: Vegan cooking; Macrobiotic diet -- Recipes; Cookbooks